PENGELOLAAN ZAKAT PERTANIAN DI LAZIS NU KABUPATEN KENDAL - Abdul Hakim (Kopertais Wilayah X Jawa Tengah, 2015)
In Kendal, at least three social religious institutions that have influence in the community of Kendal, Nahdlatul Ulama (NU), Muhammadiyah, and Rifaiyyah.. Among the three institutions, Nahdlatul Ulama (NU) has the most members spread across the region Kendal, particularly among the farming community. Ideally, NU was able to encourage its members to carry out agricultural zakat. Especially in the NU Community has an institutions, LAZIS (Institution for Managerial Zakat and Shodaqoh). But in reality, of the amount of NU LAZIS scattered in the district of Kendal, only five LAZIS that optimally perform zakat empowerment of agriculture, namely District Rowosari, District Patebon, District Gemuh, District Kangkung, and District Boja. Its implementation is not maximized in the districts but still only focused on areas of the village or certain villages Management and organization become a serious problem in the utilization of zakat agriculture . Zakat management of agriculture focused on aspects of the collection and utilization . Organizational aspects can be solved by internal and external solutions through communication , mapping mustahik and internal consolidation with LAZIS - LAZIS NU in its territory.Keywords: Management, Agricultural Zakat, LAZIS